PERANAN PEMASARAN DIGITAL DALAM MENINGKATKAN PENJUALAN PT SAHABAT JAYA SUKSES - Edalmen Edalmen; Ervina Ervina (LPPM UPN Veteran Jakarta, 2023)
PT Sahabat Jaya Sukses is incurring high marketing cost and facing declining sales. These can happen because this company is still doing offline marketing that requires high-cost, has narrow reach marketing, and has less target market’s accuracy. On the other hand, there’s a potential for this company to do online (digital) marketing that requires low-cost, reaches a wider market, and has more target market’s accuracy. This student creativity program in the form of internship as a digital marketer aims to increase the sales of PT Sahabat Jaya Sukses. This student creativity program begins with collecting data by conducting observations, interviews, and documentation related to the marketing problems in this company. Next, practice is being done by creating content designs that will be promoted through Instagram and Facebook, promoting the content designs in Instagram using Instagram ads, sharing the content designs in Facebook to various groups on Facebook that related to the target market, and creating and operating an online shop on Tokopedia. Broadly speaking, this student creativity program is able to give positive benefit for the sales of PT Sahabat Jaya Sukses, which the sales from January to May 2022 are higher than the sales from January to May 2021. Therefore, it is suggested that PT Sahabat Jaya Sukses should increase the number of employees working in the digital marketing department and respond well and fast to online questions or statements from customers with the aim of increasing the sales.